CARNOSINE AVOIDS THE OXIDATIVE DAMAGE CAUSED BY INTENSE EXERCISE ON RAT SOLEUS MUSCLE - Bortolatto, Guilherme Pedrini [UNESP]; Dias de Medeiros, Hyllana Catarine [UNESP]; Guelfi, Marieli [UNESP]; Tavares, Marco Aurelio [UNESP]; Mazzo, Meiriele [UNESP]; Mingatto, Fabio Erminio [UNESP] (Soc Brasileira Med Esporte, 2020)
Introduction: Intense physical exercise affects the balance between the production of reactive oxygen species and antioxidant defense in the muscle. Carnosine is a cytoplasmic dipeptide composed of the amino acids beta-alanine and histidine. Objective: This study aimed to evaluate the effect of carnosine and its precursor beta-alanine on oxidative damage caused by intense physical exercise in the soleus muscle of rats. Methods: Male Wistar rats weighing between 200 and 240 g were divided into four groups: control, exercise, exercise + beta-anine and exercise + carnosine.The animals from the groups that underwent the exercise ran on a treadmill for 60 minutes at 25 m/minute. Factors related to muscle damage and oxidative stress were assessed in soleus muscle homogenate and blood serum. Results: The exercise promoted muscle damage, as observed through increased serum activity of enzymes aspartate aminotransferase and creatine kinase. It also induced oxidative stress in soleus muscle, as seen by the increased activity of the enzymes glutathione peroxidase and glutathione reductase, decreased concentration of reduced glutathione, and increased concentration of malondialdehyde, an indicator of lipid peroxidation. Carnosine kept the creatine kinase, glutathione peroxidase and glutathione reductase enzyme activity values, and the concentration of reduced glutathione and malondialdehyde, close to those of the control group. Conclusion: The results indicate that pretreatment with carnosine protected the rat soleus muscle against oxidative damage and consequent injury caused by intense physical exercise.
Keywords: Antioxidants; Oxidative stress; Free radicals; Exercise test